Processo de trabalho e Educação a Distância: expansão e mudanças na universidade pública brasileira - Leonardo Zenha Cordeiro (2010)
This essay analises the changes in the organization of the work at public universities in Brazil with the introduction of on - line graduation courses.The research looks into graduation courses at Federal Universities set up by the Open University System Of Brazil. This study focuses on the education at these universities, the changes and the expasion of the EAD as well as the analisys of the organization of the scholar work and its impact on the current situation.This essay has tried to identify the organization of the work regarding the offer of courses at EAD and the professionals involved in the educational activity.It has been analised the conditions of the scholar as workers and the role they play at EAD. The study has been divided in three chapters. In the first one it has been identified all universities which offer on - line graduation courses on the open university system of Brazil`website and its legal framework. In the second chapter an on -line questionaire has been answered at 13 federal higher education institutions in teaching and bachelor`s degree courses. It has been identified the caracteristics of the work process, the materials developed by these workers the physical and financial resourses aiming at the offer of courses. The third chapter analises three graduation courses which are part of the Open University System of Brazil at three univeristies two of which are teaching degree couses and the other a Bachelor´s degree course.At this point it was used as categories of analisys the division of tasks and the routine of the work in the courses( such as meetings and the relationship with other workers).Finally it is assessed an important period in the defining of EAD and digital culture which can be found more and more in teaching and learning enviroments in today`s society present in the teacher`s reality and in the organization of the scholar work. In these study it has been important to identify the diversity of ways and flexible models to meet the demands for access to higher education.